A study on exploring the hiring preferences of selected school libraries with reference to gender - Cantal, Rowell G. (2014)
Librarianship has traditionally been seen as women's work, along with nursing and teaching school. In our society where gender became diverse, openness, readiness and acceptance of the society is in question most especially in the profession industry.